2016
DOI: 10.1080/09658211.2016.1173704
|View full text |Cite
|
Sign up to set email alerts
|

Between-language repetition priming in antonym generation: evidence that translation-equivalent adjectives have shared conceptual representations across languages

Abstract: Previous literature has demonstrated conceptual repetition priming across languages in bilinguals. This between-language priming effect is taken as evidence that translation equivalents have shared conceptual representations across languages. However, the vast majority of this research has been conducted using only concrete nouns as stimuli. The present experiment examined conceptual repetition priming within and between languages in adjectives, a part of speech not previously investigated in studies of biling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…A third perspective arises from evidence that translation equivalents share conceptual representations and that the two languages of a bilingual access a common amodal semantic or conceptual system (for reviews, see Francis, 1999, 2005). Most relevant to reasoning about long-standing semantic associations among category exemplars, studies of conceptual repetition priming between languages have shown evidence that three types of semantic associations (i.e., category-exemplar, noun-verb action, and antonym relationships) have shared representations across languages in bilinguals (de la Riva López, Francis, & García, 2012; Francis, Fernandez, & Bjork, 2010; Seger, Rabin, Desmond, & Gabrieli, 1999; Taylor & Francis, 2017). If semantic associations are in fact language-general, that is, independent of any particular language, then there should be no effects of language on their utilization and therefore no difference between L1 and L2 in the degree of semantic clustering in recall output.…”
Section: Conceptualizations Of Bilingual Proficiency and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…A third perspective arises from evidence that translation equivalents share conceptual representations and that the two languages of a bilingual access a common amodal semantic or conceptual system (for reviews, see Francis, 1999, 2005). Most relevant to reasoning about long-standing semantic associations among category exemplars, studies of conceptual repetition priming between languages have shown evidence that three types of semantic associations (i.e., category-exemplar, noun-verb action, and antonym relationships) have shared representations across languages in bilinguals (de la Riva López, Francis, & García, 2012; Francis, Fernandez, & Bjork, 2010; Seger, Rabin, Desmond, & Gabrieli, 1999; Taylor & Francis, 2017). If semantic associations are in fact language-general, that is, independent of any particular language, then there should be no effects of language on their utilization and therefore no difference between L1 and L2 in the degree of semantic clustering in recall output.…”
Section: Conceptualizations Of Bilingual Proficiency and Memorymentioning
confidence: 99%
“…Second, repetition priming in verb generation (generating an appropriate verb to a noun cue) transferred across languages in bilinguals (de la Riva López et al, 2012; Seger et al, 1999), indicating that object-action associations are shared across languages. Third, semantic processing of adjectives in one language at encoding elicited priming when generating the words as antonyms in the other language at test (Taylor & Francis, 2017), indicating that antonym relationships are shared across languages. These results taken together with the present results provide evidence that long-standing semantic associations are stored in a language-general form in the language-general conceptual system of semantic memory.…”
Section: Implications For Conceptualizations Of L2 Memorymentioning
confidence: 99%
“…There must be a comparison to a within-language repetition condition. In most studies of conceptual repetition priming, priming effects in between-language conditions were attenuated relative to priming in within-language conditions (de la Riva López et al, 2012; Francis & Goldmann, 2011; Francis et al, 2010; Smith 1991; Taylor & Francis, 2017). This phenomenon naturally leads researchers to ask whether the reduction in priming that occurs when the language changes from encoding to test is evidence for the existence of non-overlapping features at the semantic or conceptual level.…”
Section: Evidence For Shared Word Meaning Representations In Bilinguamentioning
confidence: 99%
“…The measure of priming is the reduction in response times for antonyms encountered at encoding relative to new antonyms. Repetition priming between languages in antonym generation was substantial in a study that used adjectives as stimulus words (Taylor & Francis, 2017). For example, rating the word grande on pleasantness at encoding speeded the generation of its translation equivalent large as an antonym to small at test.…”
Section: Evidence For Shared Word Meaning Representations In Bilinguamentioning
confidence: 99%
See 1 more Smart Citation